The power of cabinet appointments in autocracies: elite cooptation and anti-regime mass uprisings - Kavasoglu, Berker (The journal of conflict resolution, 2024)
Why are some autocratic regimes more prone to mass uprisings than others? This article argues that autocratic leaders can mitigate opposition mobilization by strategically appointing opposition leaders to cabinet positions. Drawing on yearly data from autocracies between 1966 and 2020, the article exploits temporal variations in the composition of cabinets and the onset of mass uprisings within autocratic regimes. The findings demonstrate that appointing opposition elites to cabinet positions significantly decreases the likelihood of anti-regime mass uprisings. The results are robust across alternative model specifications and estimation strategies addressing endogeneity concerns. By demonstrating why some autocracies with organized opposition avoid uprisings while others face repeated challenges, this study offers novel insights into how opposition cooptation stabilizes autocratic regimes.
Gesehen am 10.06.2025